A diversidade cultural e a sua influ??ncia na gest??o de equipes de projetos globais de empresas multinacionais - Lima, N??dia (2016)
The influence of culture in organizations has been the focus of research and studies since a long time ago, and the reason is that culture shapes decision patterns of a company, guides their actions and directs the individual behavior of all the organization???s professionals. In the project environment, interactions between the project managers and team members may also be affected by variables such as culture and the projects manager's leadership style. Focused in this context, the aim of this study is to assess how the cultural diversity of global project???s members of multinational companies can influence the projects manager???s management skills. Therefore, this study presents issues about project management and management of global project teams and also references about concepts and approaches of culture, highlighting the cultural diversity. This study is a qualitative and descriptive multiple case, that was conducted in multinational companies. The main purposes of this study are collaborate with other research on culture in the project management environment, and contribute to a better understanding on how project managers can deal with the influence of cultural diversity in the management of global projects team.The results of this research demonstrate that the different cultural characteristics (language, values, religion and others) of the members of a global project can influence both negative and positive the management ability of global project managers and that managers of such projects have to deal with a number of challenges that require various personal skills and social relationships, and the adoption of measures to minimize potential problems in this context. Thus, the main contributions of this study are provide a better understanding of how project managers can handle the influence of cultural diversity in the management of global project teams as well as collaborate with future research on culture in the project management environment.